O valor numérico da expressão abaixo para a = 3, b = 5 e c = 1 é:
![\frac{a}{ \sqrt{b} \: + \: c } \frac{a}{ \sqrt{b} \: + \: c }](https://tex.z-dn.net/?f=+%5Cfrac%7Ba%7D%7B+%5Csqrt%7Bb%7D+%5C%3A+%2B+%5C%3A+c+%7D+)
A.
![\sqrt{5} + 1 \sqrt{5} + 1](https://tex.z-dn.net/?f=+%5Csqrt%7B5%7D+%2B+1)
B.
![2.( \sqrt{3} + 4) 2.( \sqrt{3} + 4)](https://tex.z-dn.net/?f=2.%28+%5Csqrt%7B3%7D+%2B+4%29)
C.
![\frac{3.( \sqrt{5} - 1)}{4} \frac{3.( \sqrt{5} - 1)}{4}](https://tex.z-dn.net/?f=+%5Cfrac%7B3.%28+%5Csqrt%7B5%7D+-+1%29%7D%7B4%7D+)
D.
![\frac{5.( \sqrt{3} + 5)}{3} \frac{5.( \sqrt{3} + 5)}{3}](https://tex.z-dn.net/?f=+%5Cfrac%7B5.%28+%5Csqrt%7B3%7D+%2B+5%29%7D%7B3%7D+)
E.
Soluções para a tarefa
Respondido por
1
a (√b-c) a√b - ac 3√5 - 3 3(√5 - 1)(√5 + 1) 3.(5 - 1) 12 ____________ = _______ = ________= ____________ = ______=__= 3
5
(√b+c) (√b-c) √b - c² √5 - 1² (√5 - 1)( √5 + 1 ) 5 - 1 4
5
(√b+c) (√b-c) √b - c² √5 - 1² (√5 - 1)( √5 + 1 ) 5 - 1 4
silveiraluiz28p0gv25:
Nao entendi muito bem, mas obrigado!
Perguntas interessantes
Matemática,
11 meses atrás
Inglês,
11 meses atrás
Matemática,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás
Física,
1 ano atrás
Biologia,
1 ano atrás